A PARADIGM ON INDIGENOUS COUNSELING OF SPIRITUALITY IN PESANTREN EDUCATION CULTURE - Arina Mufrihah; Juntika Nurihsan (UIN Sunan Kalijaga Yogyakarta, 2025)
The paradigm shift from colonialism to postcolonialism has a remarkable contribution on the construction of indigenous counseling foundations that presented an epistemology derived from local wisdom. Indigenous counseling recognizes universal standards of truth depend on cultural and subcultural values and knowledge, which do not have to be subject to the recognition and validation of Western rationalities. Indigenous counseling builds knowledge of the interconnection and interdependence dimensions, the relationship between humans transcends the physical world. Indigenous Counseling of Spirituality in Pesantren education culture is a paradigm that proposes views on human nature, theoretical foundations, and how counseling is aligned with the world view of the pesantren community spirituality. The philosophy of postcolonialism is functioned as the cornerstone of indigenous counseling in general, while Sunni philosophy is a paradigm of thinking to construct indigenous counseling of spirituality in pesantren education culture. Keywords: Counseling paradigm, cultural values, indigenous counseling, pesantren education, spiritual counseling.